Rolling Horizon-Based Operation Optimisation of Energy Storage Systems and Electric Vehicles Integrated in Distribution Networks - Yildiz, Husna; Ozdemir, Hilal; Erdinc, Ozan; Pisica, Ioana (IEEE, 2024)
Effective management algorithms have emerged to mitigate the adverse effects of high renewable energy systems and electric vehicle (EV) penetration on distribution networks. This study proposes a rolling horizon optimization-based approach to reduce power loss in distribution networks that incorporate EVs, battery-based energy storage systems (BESS) and photovoltaic (PV) plants. This approach entails an efficient charging algorithm for EVs and BESS, formulated as a mixed-integer linear programming (MILP) model and the power loss equation is linearized using a piecewise approach with the Special Ordered Sets of Type 2 (SOS2) method. The algorithm accounts for uncertainties related to EV charging and PV generation, yielding promising results. Our findings indicate that utilizing BESS and effectively managing EV charging profiles can be leveraged to reduce the power loss on the PV-integrated distribution systems. Also, the effects of the location of BESS and EV parking lot on the network are analysed thoroughly and even a decrease of 7.6% in power loss is evidenced due to the relocation of the EV parking lot between feeders.
Keywords: Battery-based energy storage systems; electric vehicles parking lot; rolling horizon optimization; Energy & Fuels; Engineering